Towards a Taxonomy of Workplace "Pressure" in Complex, Volatile, and Emergency Situations. Issue Volume 34:Issue s1(2019) (May 2019) - Calahorrano, Alicia Zavala; Plummer, David; Day, Gary
Abstract : Introduction: Pressure in the workplace has been studied in a number of settings. Many studies have examined pressure from physiological and psychological perspectives, mainly through studies on stress. Performing under pressure is a fundamentally important workplace issue, not least for complex, volatile, and emergency situations. Aim: This research aims to better understand performance under pressure as experienced by health and emergency staff in the workplace. Methods: Three basic questions underpin the work: (1) how do health and emergency workers experience and make sense of the 'pressures' entailed in their jobs? (2) What impacts do these pressures have on their working lives and work performance, both positively and negatively? (3) Can we develop a useful explanatory model for 'working under pressure' in complex, volatile, and emergency situations? The present paper addresses the first question regarding the nature of pressure; a subsequent paper will address the question of its impact on performance. Using detailed interviews with workers in a range of roles and from diverse settings across Ecuador, this study set out to better understand the genesis of pressure, how people respond to it, and to gain insights into managing it more effectively, especially with a view to reducing workplace errors and staff burnout. Rather than imposing preformulated definitions of either 'pressure' or 'performance, ' we took an emic approach to gain a fresh understanding of how workers themselves experience, describe and make sense of workplace pressure. Results: This paper catalogs a wide range of pressures as experienced by our participants and maps relationships between them. Discussion: We argue that while individuals are often held responsible for workplace errors, both 'pressure' and 'performance' are multifactorial, involving individuals, teams, case complexity, expertise, and organizational systems, and these must be taken into account in order to gain better understandings of performing under pressure.